1993
DOI: 10.1017/s0022215100123795
|View full text |Cite
|
Sign up to set email alerts
|

Audit of the incidence of persistent perforation of the tympanic membrane following grommet removal or extrusion

Abstract: The incidence of persistent perforation following grommet removal or extrusion in 210 ears was assessed, and found to be zero per cent. Collar button grommets were retained longer than Shepard grommets, and the percentage of ears requiring two or more tube insertions was 51.9 per cent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The overall prevalence is approximately 3% [25], and it is basically associated to the retention time and the number of tube insertions. Conventional fluoroplastic grommets are believed to cause fewer perforations, ranging from 0 to 3% of insertions [6,36,70,72,77]. The overwhelming majority of these perforations heal completely, while persistent perforation is reported in approximately 1.4% of cases [41,42].…”
Section: Perforationmentioning
confidence: 99%
“…The overall prevalence is approximately 3% [25], and it is basically associated to the retention time and the number of tube insertions. Conventional fluoroplastic grommets are believed to cause fewer perforations, ranging from 0 to 3% of insertions [6,36,70,72,77]. The overwhelming majority of these perforations heal completely, while persistent perforation is reported in approximately 1.4% of cases [41,42].…”
Section: Perforationmentioning
confidence: 99%
“…We found that 36.4 per cent of tubes had extruded after 12 months and 71.0 per cent after 24 months. Todd reported an audit of 186 ears in which 91.4 per cent of Shepard tubes had extruded after 12 months 11 . Gibb et al reported equivalent results for Shepard tubes.…”
Section: Discussionmentioning
confidence: 99%
“…11 Gibb et al reported equivalent results for Shepard tubes. We found that 36.4 per cent of tubes had extruded after 12 months and 71.0 per cent after 24 months.…”
Section: Time To Extrusionmentioning
confidence: 93%
“…Persistent perforation after tube extrusion (9)(10)(11)37,38,41,42) Scarring of the tympanic membrane (1,37,38) Atrophic monomeric TM (1,37,38) Granuloma (37,38) Tympanosclerosis (1,37) Cholesteatoma (1,37,38) Migration of tympanostomy tube into middle ear canal (37) Complications of TT may be divided into two groups. The first group includes early complications, which occur while the tube is in place and patent and appear to be directly related to the tube.…”
Section: Late Complicationsmentioning
confidence: 99%
“…This is less common than tympanosclerosis, with the rate of perforation ranging from 0.5 to 25 percent depending on the type of tube and the number of tubes inserted into the same tympanic membrane over time. Long term tubes have the highest rate of tympanic membrane perforation and short term tubes have a lower frequency (41,42). No preoperative factor completely predicts the development of perforation (43).…”
Section: Tympanic Membrane Perforationmentioning
confidence: 99%